2021
DOI: 10.1097/mop.0000000000001069
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide epidemiology of neuro-coronavirus disease in children: lessons for the next pandemic

Abstract: Purpose of review The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic has overwhelmed the global community, negatively impacting patient health and research efforts; associated neurological manifestations are a significant cause of morbidity. This review outlines the worldwide epidemiology of neurologic manifestations of different SARS-CoV-2 clinical pediatric phenotypes, including acute coronavirus disease 2019 (COVID-19), multisystem inflammatory syndrome in children (MIS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 90 publications
1
18
1
Order By: Relevance
“…[ 24 , 26 , 56 , 57 ] However, a study reported that the frequency of seizures increased in young children, occurring at a rate of 38% under the age of 5 years. [ 11 ] Our study findings are inconsistent with literature reports as most of our patients were over 9 years. In addition; the number of children below 2 years was equal to the number of children above 9 years in the seizure group.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…[ 24 , 26 , 56 , 57 ] However, a study reported that the frequency of seizures increased in young children, occurring at a rate of 38% under the age of 5 years. [ 11 ] Our study findings are inconsistent with literature reports as most of our patients were over 9 years. In addition; the number of children below 2 years was equal to the number of children above 9 years in the seizure group.…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, neurological findings are more common in obese patients in the literature. [6,9–12,15,23,26,53–55]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurological symptoms have been identified in paediatric cases of COVID-19 [5], with approximately 22% of hospitalized children being affected by neurological manifestations such as smell/taste disorders, headache, and stroke [6]. Intracranial hypertension [7] and acute encephalitis [8] have also been reported in children with multisystem inflammatory syndrome.…”
Section: Introductionmentioning
confidence: 99%